Psychology hardiness and psychology well-being of banking sector employees and moderating role of coping strategy - Munusamy, Agilan; Adam Assim, Mohd Ibrani Shahrimin (UKM Press, 2019)
Employees are one of the most important assets for country where its organization's structure determines the way these employees are interrelated and their teamwork in achieving the mission and the goal of the company which leads the employees to deal with stress in their personal life most likely in workplace. Stress can be accumulative over a period of time resulting in a "burnout experience" and it leads to physical and psychological ill-health adversely affecting work and social functioning.The objective of this study is to explore and investigate the coping strategy as a moderating effect in predicting psychology hardiness and psychology well-being among employees from Malaysian banking sector. This study also intended to determine correlation and the statistic significant differences in the respondents’ psychology hardiness by demographic factors such as gender. The survey was executed at 11 Banks and 141 respondents were participated in Kuala Lumpur which includes both Malaysian and the international banks as well. Psychology hardiness was measured using the dispositional Resilience [DRS-15 (v3.2)] scale, Coping strategy was measured using the Problem Oriented Brief Coping Experienced (BRIEF COPE) scale while Psychology well-being was measured using Well-being Manifestation Measure scale (WBMMS) scale. In the study,all three variables are score variable therefore the hypotheses were tested by using hierarchical multiple regression, Correlation and T-Test in SPSS version 20. The results of the study revealed that coping strategy enhances the effect of psychology hardiness on wellbeing. And, as a moderator coping strategy would increase the effect of psychological hardiness on employees' well-being in the banking sector.